2012
DOI: 10.1007/s11270-012-1158-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Stomatal Conductance for Estimating Ozone Uptake of Fagus crenata Under Experimentally Enhanced Free-air Ozone Exposure

Abstract: We examined a performance of the multiplicative stomatal conductance model to estimate the stomatal ozone uptake for Fagus crenata. Parameterization of the model was carried out by in-situ measurements in a free-air ozone exposure experiment. The model performed fairly well under ambient conditions, with low ozone concentration. However, the model overestimated stomatal conductance under enhanced ozone condition due to ozone-induced stomatal closure. A revised model that included a parameter representing ozone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
2
24
4
Order By: Relevance
“…For example, a critical level can be defined as a 26 "concentration, cumulative exposure or cumulative stomatal flux of atmospheric pollutants 27 above which direct adverse effects on sensitive vegetation may occur according to present The actual damage, however, does not depend on concentrations, but on the amount of O 3 that 8 enters the plant, the capability of the plant's defense system, and the plant's sensitivity to 9 oxidative stress (Sharma et al 2012). The transport into the foliage occurs almost exclusively 10 through stomata, which also regulate CO 2 uptake while preventing desiccation.…”
mentioning
confidence: 99%
“…For example, a critical level can be defined as a 26 "concentration, cumulative exposure or cumulative stomatal flux of atmospheric pollutants 27 above which direct adverse effects on sensitive vegetation may occur according to present The actual damage, however, does not depend on concentrations, but on the amount of O 3 that 8 enters the plant, the capability of the plant's defense system, and the plant's sensitivity to 9 oxidative stress (Sharma et al 2012). The transport into the foliage occurs almost exclusively 10 through stomata, which also regulate CO 2 uptake while preventing desiccation.…”
mentioning
confidence: 99%
“…Parameter estimation was carried out using a boundary line analysis (e.g., Alonso et al, 2008;Hoshika et al, 2012b (Alonso et al, 2008). We took f min as mean value less than the 5 th percentile values of conductance.…”
Section: Parameterization Of the Stomatal Conductance Modelmentioning
confidence: 99%
“…Hoshika et al (2012b) tried to parameterize O 3 -induced stomatal closure based on stomatal conductance data during 3-month exposure to O 3 in 2011. They reported that stomatal conductance was decreased with increasing cumulative O 3 exposure or uptake.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations